Persepsi Masyarakat Terhadap Pemanfaatan Humus dari Tahura Untuk Pemanfaatan Pupuk Organik Bagi Areal Pertanian Masyarakat di Desa Tongkoh Kabupaten Karo - Muhammad Zarkasyi Habiby; Budi Utomo; Afifuddin Dalimunthe (Program studi Kehutanan USU, 2015)
This study aimed to determine the direct perception of society towards organic fertilizers and forests as well as the way society treated farm wastes in the village of Dolat Rayat Tongkoh District of Karo. The method used in this research was a survey research methods. The results showed that the level of public perception in the Tongkoh village, Dolat Rayat District, Karo of the existence and functions of forests and the use of fertilizers at high category, respectively by 75 % and 93.75 %. Alternative most decisive election of respondents associated with the treatment of agricultural waste was to be burned with the percentage of 49.3 %.Key word: Forest , Organic Fertilizer , Public Perception